The Dynamics of Peaceful and Violent Protests in Hong Kong - Lo, Sonny Shiu-Hing. author. aut Link
XV, 383 p. 8 illus.
Keywords: This book shows that Hong Kong’s protests from June to December 2019 originated from not only an attempt to extradite a Hong Kong man involved in a Taiwan murder case, but also China’s effort at extraditing corrupt mainlanders who laundered dirty money in the territory. The mixture of peaceful and violent protests was due to the snowballing effect of protestors-police confrontations, the imbalanced way in which police exercised their power, and protestors’ strategies. The protests triggered the national security concerns of Beijing, which mobilized the People’s Armed Police to Shenzhen as a warning rather than sending them openly to Hong Kong to avoid undermining the image of “one country, two systems.” The entire debate raised the concerns of Washington, Taiwan, and foreign governments, heightening Beijing’s sensitivity. After the bill was withdrawn, the anti-extradition movement has become anti-police and anti-mainland, constantly challenging the legitimacy of the Hong Kong government and Beijing. This is a valuable read for China watchers, political scientists and all those interested in the future of East Asia. Sonny Shiu-Hing Lo is Professor at HKU SPACE, Hong Kong. He was President of the Hong Kong Political Science Association from 2014 to 2018. Steven Chung-Fun Hung is Assistant Professor at the Education University of Hong Kong and his research focuses on Hong Kong’s education, politics, and cultural history. Jeff Hai-Chi Loo is a doctoral student at University of Waterloo, Canada, and his research interests include populism, social movement, Taiwan and Hong Kong politics.